Salas de Recursos Multifuncionais: um estudo sobre a formação e a atuação de professores - Camargo, Miriam Rosa Torres de (Universidade Federal de São Carlos, 2014)
The present study aimed to investigate aspects of the formation and action of teachers, working with pupils with special educational needs, in inclusive perspective, in multifunctional resource rooms, specifically in the city of Sorocaba- SP. The specific objectives included: the possibilities and challenges perceived by teachers working in SEM; investigation as to how the educators felt and acted in the face of difficulties encountered in educational practice; and evaluation, according to the existing continuing education, offered by the Department of Education through the Center for Excellence in Education - Don Jose Lambertt. Four teachers, working in multifunctional features, participated in this study. The procedures used were: semistructured interviews, participant observation, records from field diaries and document research. The results were analysed based on four axes: the profile of teachers of specialized educational services (AEE), subsequent to their initial training offered by Pedagogy courses; the challenges and possibilities facing teachers within Specialized Educational Services (ESA), in the Multi-Functional Room Appeal (SRM); the articulation between the meaning of skilled labor and teaching practices; and the perceptions of on-going education promoted by the Department of Education (SEDU) / Reference Center for Education (CRE). These axes have some major aspects, some of which have been highlighted: the importance of continuing education, according to the teachers interviewed; and the contribution and limitations of this proposal in terms of their teaching practices, in the use of multi-functional rooms. In conclusion, despite the weaknesses of continuing educational programs for teachers of SRMs, there have still been major advances and the participants themselves recognize how these formations can influence the way we act towards the obstacles encountered in the daily lives of SRMs.
Multi-functional resources: a study on the formation and operation of teachers
Keywords: Sala de Recursos Multifuncionais; Multi-functional resource rooms; Professores - formação; Teachers - In-service training; Teachers, Training of; Educação especial; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO